PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU UNTUK SISWA SEKOLAH DASAR MENGGUNAKAN MODEL DICK AND CAREYPENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU UNTUK SISWA SEKOLAH DASAR MENGGUNAKAN MODEL DICK AND CAREYPENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TER: Pembelajaran terpadu, Modul, Media (Power Point), Panduan Siswa, Panduan Guru - Karyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2021)
Abstract The research aims to develop the integrated sciences learning device for sixth grade elementary school semester I, such as a module, PowerPoint media, Student Guide, and Teacher Guide. The research and development method used Dick and Carey model throughout nine of ten development stages. The instrument is questionnaires and achievement tests with an Alpha Cronbach reliability coefficient of 0.76.Â The formative evaluation through validated by the expert judgment involved the content expert and instructional design expert. Meanwhile, one-to-one validation involved a student and teacher of the elementary school in Elementary Schools Group III in Seruyan Hilir Sub-district, Seruyan District, Central Kalimantan. The result of the content expert judgment, the instructional design expert, and one-to-one validations involved a student and teacher showed the high quality of the instructional device. The result of small group validation showed that the students achieve mastery learning of 100% with the minimal mastery learning criteria of 60 and an average post-test score of 82.33. The instructional device of Integrated Science for the sixth grade of Elementary School Semester I has worthy used in learning of the elementary school.